Consensus development for healthcare professionals - Kea, Bory (Intern Emerg Med, 2014)
Consensus development sprang from a desire to synthesize clinician and expert opinions on clinical practice and research agendas in the 1950s. And since the American Institute of Medicine formally defined “guidelines” in 1990, there has been a proliferation of clinical practice guidelines (CPG) both formally and informally. This modern decision making tool used by both physicians and patients, requires extensive planning to meet the challenges of consensus development while reaping its rewards. Consensus allows for a group approach with multiple experts sharing ideas to form consensus on topics ranging from appropriateness of procedures to research agenda development. Disagreements can shed light on areas of controversy and launch further discussions. It has five main components: three inputs (defining the task, participant identification and recruitment, and information synthesis), the approach (consensus development by explicit or implicit means), and the output (dissemination of results). Each aspect requires extensive planning a priori as they influence the entire process, from how information will be interpreted, the interaction of participants, the resulting judgment, to whether there will be uptake of results. Implicit approaches utilize qualitative methods and/or a simple voting structure of majority wins, and are used in informal consensus development methods and consensus development conferences. Explicit approaches aggregate results or judgments using explicit rules set a priori with definitions of “agreement” or consensus. Because the implicit process can be more opaque, unforeseen challenges can emerge such as the undue influence of a minority. And yet, the logistics of explicit approaches may be more time consuming and not appropriate when speed is a priority. In determining which method to use, it is important to understand the pros and cons of the different approaches and how it will affect the overall input, approach, and outcome.